H2O2 drives the transition from conchocelis to conchosporangia in the red alga Pyropia haitanensis with promotion facilitated by 1-Aminocyclopropane-1-carboxylic acid - Niu, Tingting; Qian, Haike; Chen, Haimin; Luo, Qijun; Chen, Juanjuan; Yang, Rui; Zhang, Peng; Wang, Tiegan (Frontiers in Plant Science, 2024)
The Bangiales represent an ancient lineage within red algae that are characterized by a life history featuring a special transitional stage from diploid to haploid known as the conchosporangia stage. However, the regulatory mechanisms governing the initiation of this stage by changes in environmental conditions are not well understood. In this study, H2O2 was shown to be the key signal initiating the transition from conchocelis to conchosporangia in Pyropia haitanensis. Phytohormone analysis showed a significant increase in 1-aminocylopropane-1-carboxylic acid (ACC) levels during conchosporangia maturation, while changes in environmental conditions were found to promote the rapid release of H2O2. H2O2 induction led to conchosporangia development, and ACC enhanced both H2O2 production and conchosporangia development. This promotive effect was inhibited by the NADPH oxidase inhibitor diphenylene iodonium and the H2O2 scavenger N, N'-dimethylthiourea. The balance of oxidative-antioxidative mechanisms was maintained by regulating the activities and transcriptional levels of enzymes involved in H2O2 production and scavenging. Transcriptome analysis in conjunction with evaluation of enzyme and transcription level changes revealed upregulation of protein and sugar synthesis along with modulation of energy supply under the conditions that induced maturation, and exogenous ACC was found to enhance the entire process. Overall, this study demonstrates that ACC enhances H2O2 promotion of the life cycle switch responsible for the transition from a vegetative conchocelis to a meiosis-preceding conchosporangia stage in Bangiales species.